Chinese collective foster care model: Description and evaluation. (March 2017) - Wang, Wen-Chi; McCall, Robert B; Li, Junlei; Groark, Christina J; Zeng, Fanlin; Hu, Xiaolin
Family environments are known to usually be better for children's development than institutional care. China has experience with different forms of foster care, but none have been empirically evaluated, especially with respect to children's outcomes. One form of foster care is 'collective fostering', in which many foster families live in a single apartment building on the grounds of the institution. The goal of this study was to evaluate the effectiveness of such a project operated by a children's institution in a large city in China by examining changes in children's height and weight from before to after entering foster care. Results ( n = 102, mean age = 63 months) showed a significant positive quadratic relationship between time and height ( p = .002), with height z -scores declining during institutional residency and then increasing after entering foster care. Further analysis on children ( n = 23) who were enrolled in the fostering project for more than 65 months showed that their height and weight z -scores improved significantly while living in foster families compared to the last assessment before the transition. The study concluded that the collective foster care project, like the more widely practiced community foster care, had the potential for improving children's development.